Analisis Pengaruh Waktu Torefaksi Terhadap Kualitas Biobriket dari Cangkang Kelapa Sawit (Palm Oil Shell) - Oki Alfernando; Lince Muis; Siti Junaida; Malem K. Ginting; Muhammad Haviz (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
Palm oil shells are solid waste from the palm oil processing industry. In 1 ton of palm oil produces 6.5% shell waste. Solid waste can be converted into fuel as a substitute for oil, namely bio-briquettes as an alternative fuel through a combustion process with less air. This study aims to determine the effect of time variations on the quality and yield of bio-briquettes produced using a combined pretreatment method of densification (with additional binder) and torrefaction at a temperature of 275 oC and time variations of 30, 45, 60, 75 and 90 minutes. Torrefaction is a new method in the briquetting process where this method takes place at low temperatures. The results showed that the longer the torrefaction time, in general, the value of water content, ash content, volatile matter content, fixed carbon value and burning time also increased. However, this is inversely proportional to the yield value of the resulting product, so the best quality is obtained in 75 minutes with a moisture content of 0.86%, ash content 2.38%, volatile matter content 18.23%, fixed carbon value 78.51 %, product yield is 36.3165% and calorific value is 5964 Kcal/kg.